Wacław Sieroszewski and Problems of European Identity - Sadowska, Ida (Respectus Philologicus, 2006)
This article presents two novels: "At the Edge of the Forests" (1894) and "Overseas Devil" (1902) written by Wacław Sieroszewski. The writer was regarded as the most interesting representative of exotic literature during the Young Poland period. The issue which the author of the article has concentrated her attention on is not connected with representation of specificity of exoticness manifested in Sieroszewski's work. However, the main problem concerns dilemmas connected with a sense of European identity of Polish characters in Sieroszewski's prose. The texts from both novels are discussed as a literary testimony of Polish consciousness that is related with the Northern East Siberia and the Far East at the turn of the centuries. The phenomenon of the merge of the two perspectives has appeared in the novels, i.e. a Polish exile and a European explorer. Biographical and historical-political context of both novels has been taken into consideration. The author discusses the identity components of Polish characters which became evident at the moment of confrontation of the Asian culture and civilization; which way Sieroszewski judged them; why Sieroszewski's characters are not always identified with the European tradition.
Keywords: European identity; Siberia; Far East; exotic literature; journey; Young Poland's novel